2017
DOI: 10.1186/s12870-017-1010-x
|View full text |Cite
|
Sign up to set email alerts
|

Root morphogenic pathways in Eucalyptus grandis are modified by the activity of protein arginine methyltransferases

Abstract: BackgroundMethylation of proteins at arginine residues, catalysed by members of the protein arginine methyltransferase (PRMT) family, is crucial for the regulation of gene transcription and for protein function in eukaryotic organisms. Inhibition of the activity of PRMTs in annual model plants has demonstrated wide-ranging involvement of PRMTs in key plant developmental processes, however, PRMTs have not been characterised or studied in long-lived tree species.ResultsTaking advantage of the recently available … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…Recently, methylation has been found on tubulins occurring in lysine and arginine amino acid residues [22,75,76,77,78,79,80] and it has not been characterized in detail.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, methylation has been found on tubulins occurring in lysine and arginine amino acid residues [22,75,76,77,78,79,80] and it has not been characterized in detail.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, several lines of evidence [22,76,77,78] suggested that α- and β-tubulins undergo monomethylation or asymmetrical dimethylation in ω-N manner at specific arginine residues. To define methylation pattern occurring in P. lividus tubulins, sequence and pattern recognition analyses were carried out to map and characterize the amino acid residues putatively methylable and the kind of modification (monomethylarginine, MMA; asymmetric dimethylarginine, ADMA, or symmetric dimethylarginine, SDMA) (Table 5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PRMTs have also been identified in non-mammalian animals, filamentous fungi, yeasts, plants and protozoan parasites (McBride et al ., 2007; Ahmad et al ., 2011; Fisk and Read, 2011; Zhao et al ., 2016; Hadjikyriacou and Clarke, 2017; Plett et al ., 2017; Wang et al ., 2017; Bauer et al ., 2019). Enzymes similar to mammalian PRMT1, 3 and 5 are present in different eukaryotic organisms, whereas other PRMTs, such as PRMT2 and 8, are less conserved and it has been suggested that they could have evolved in the multicellular organisms as a requirement for tissue-specific functions (Bachand, 2007).…”
Section: Protein Arginine Methyltransferases (Prmts)mentioning
confidence: 99%
“…CID5380390 and CID2818500 were found to produce the strongest inhibition with IC 50 values of 23 and 11 μM, respectively [ 209 ]. CID5380390 was used to characterize PRMT activity in E. grandis roots [ 211 ]. However, no further studies have been published on the mechanism of action for either of these inhibitors.…”
Section: Implications For Cancer Treatmentmentioning
confidence: 99%